Mejoramiento genético. Mejoramiento de caracteres. Potencial de rendimiento - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1986)
Studies on yield potential continued at CIAT with the reevaluation of agronomic practices for max. yield. A considerable effort was invested in the production of erect, type IIa lines. Unfortunately, these lines have not shown the yield potential expected, possibly due to their erect habit, which makes them incapable of achieving full canopy cover at the 60-cm row spacings used at CIAT. Several expt. were conducted to compare a large range of materials at 20, 30, 45, and 60 cm-row spacings. In subsequent expt., the 41 most promising lines from previous screenings for earliness indicated a high correlation between yield, crop dry wt., and days to maturity. (CIAT)